PKM Pemberdayaan Masyarakat Pesisir Dalam Melestarikan Mangrove Di Desa Jayakarsa Kecamatan Likupang Barat Kabupaten Minahasa Utara (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Abstract The problem is how the community manages natural resources which will be very helpful in designing effective management strategies, keeping natural resources sustainable and able to meet the needs of the local community. The purpose of PKM activities is for the community to understand and understand the need for efforts to preserve the remaining mangrove forests. The method of implementing PKM activities consists of several stages: 1. Approaching government officials in Jayakarsa Village to obtain permits for the implementation of activities. 2. Carry out activities according to the scheduled time by providing material in the form of counseling and lectures. 3. Participation expected from partners is awareness, ability and motivation to accept the material to be delivered which is marked by the presence and seriousness of attending counseling and lectures from the PKM Team so that it is hoped that they will be able to apply this material. There are still people who do not know and do not understand the functions and benefits of mangrove forests. Efforts to improve and preserve mangrove forests require community involvement, especially those who live around coastal areas. Mangrove replanting involves the community in nursery, planting and maintenance, as well as conservation-based use. This model benefits the community through the availability of job opportunities so as to increase their income. Environmental conservation and efforts to prevent damage to mangrove forests are very good. This is because the surrounding community participates in environmental conservation, especially mangrove forests, so that people feel very happy in doing good things in preserving mangrove forests in Jayakarsa Village.